The Times They Are a-Changing … or Are They Not? A Comparison of Gender Stereotypes, 1983–2014. (September 2016) - Haines, Elizabeth L.; Deaux, Kay; Lofaro, Nicole
During the past 30 years, women's participation in the workforce, in athletics, and in professional education has increased, while men's activities have been more stable. Have gender stereotypes changed over this time period to reflect the new realities? And, to what extent does gender stereotyping exist today? We address these questions by comparing data collected in the early 1980s to new data collected in 2014. In each study, participants rated the likelihood that a typical man or woman has a set of gendered characteristics (traits, role behaviors, occupations, and physical characteristics). Results indicate that people perceive strong differences between men and women on stereotype components today, as they did in the past. Comparisons between the two time periods show stability of gender stereotypes across all components except female gender roles, which showed a significant increase in gender stereotyping. These results attest to the durability of basic stereotypes about how men and women are perceived to differ, despite changes in the participation and acceptance of women and men in nontraditional domains. Because gender stereotypes are apparently so deeply embedded in our society, those in a position to evaluate women and men, as well as women and men themselves, need to be constantly vigilant to the possible influence of stereotypes on their judgments, choices, and actions. Online slides for instructors who want to use this article for teaching are available on PWQ's website athttp://pwq.sagepub.com/supplemental